The Labour Force Status of Transgender People and The Impact of Removing Surgical Requirements to Change Gender on ID Documents - Samuel Mann (Global Labor Organization (GLO), 2020)
This paper uses data from the BRFSS over the period 2014-2019 to analyse the impact of removing surgical requirements to change legal gender. In many states transgender people are forced to undergo surgical procedures if they wish to change their gender on ID documents, which can be invasive, expensive, and is not always desired. In the present work state variation in the timing of the removal of surgical requirements is exploited within a triple difference framework to analyse the causal impact of these removals on the labour force participation and employment of transgender people. The findings highlight the detrimental economic impact of surgical requirements for transgender people to be able to reassign gender on birth certificates, especially for those individuals that are least likely to be able to afford surgical treatment.
Keywords: J15; J16; J71; J78; K31; K38; 330; Gender Identity; Trans; Employment; Self-Employment; Discrimination; Law; Birth Certificates